Notes and Comments the Amsterdam Auction - Goeree, Jacob K.; Offerman, Theo (Econometrica, 2004)
The Amsterdam auction has been used to sell real estate in the Dutch capital for centuries. By awarding a premium to the highest losing bidder, the Amsterdam auction favors weak bidders without having the implementation difficulties of Myerson's (1981) optimal auction. In a series of experiments, we compare the standard first-price and English auctions, the optimal auction, and two variants of the Amsterdam auction. With strongly asymmetric bidders, the second-price Amsterdam auction raises substantially more revenues than standard formats and only slightly less than the optimal auction. Copyright Econometric Society 2004.